A 3D printing Short Course: A Case Study for Applications in the Geoscience Teaching and Communication for Specialists and Non-experts - Ishutov, Sergey; Hodder, Kevin; Chalaturnyk, Rick; Zambrano-Narvaez, Gonzalo (Frontiers in Earth Science, 2021)
3D printing appeared as a prototyping method in the early 1980s, yet it is considered as a 21st century technology for transforming digital models into tangible objects. 3D printing has recently become a critical tool in the geoscience research, education, and technical communication due to the expansion of the market for 3D printers and materials. 3D printing changes the perception of how we interact with our data and how we explain our science to non-experts, researchers, educators, and stakeholders. Hence, a one-day short course was developed and delivered to a group of professors, students, postdoctoral fellows, and technical staff to present the application of 3D printing in teaching and communication concepts in the geoscience. This case study was aimed at evaluating how a diverse group of participants with geoscience and engineering background and no prior experience with computer-aided modeling (CAD) or 3D printing could understand the principles of different 3D printing techniques and apply these methods in their respective disciplines. In addition, the course evaluation questionnaire allowed us to assess human perception of tangible and digital models and to demonstrate the effectiveness of 3D printing in data communication. The course involves five modules: 1) an introduction lecture on the 3D printing methods and materials; 2) an individual CAD modeling exercise; 3) a tour to 3D printing facilities with hands-on experience on model processing; 4) a tour to experimental facilities where 3D-printed models are tested; and 5) group activities based on the examples of how to apply 3D printing in current or future geoscience research and teaching. The participants had a unique opportunity to create a digital design at the beginning of the course using CAD software, analyze it and 3D print the final model at the end of the course. This opportunity particularly helped the students to understand rendering algorithms that can be used as a learning aid. Professors gained experience in rapid preparation of visual aids for teaching. 3D printing is an emerging tool in the geoscience research, because it provides insights of how to integrate the digital data sets with 3D-printed models to support societal and technical objectives.